Evaluation of proximate composition and pasting properties of high quality cassava flour (HQCF) from cassava genotypes (Manihot esculenta Crantz) of b-carotene-enriched roots - Alamu, Emmanuel Oladeji; Maziya-Dixon, B.B.; Dixon, A. (Elsevier, 2017)
Cassava farmers are yet to fully exploit its full potential in terms of improvement of livelihood. Forty-five genotypes of cassava genotypes were processed into High Quality Cassava Flour (HQCF). These genotypes were planted in two sets, set 1 comprised 22 clones of β-carotene enriched roots and 3 check clones of white roots and set 2 comprised 18 clones and 2 check clones. The effects of variety on the proximate composition and pasting profile of the flour were investigated. The starch content ranged between 67.1 g/100 g (for 01/1663) and 82.4 g/100 g (for 30572) in set 1 and between 69.6 (01/1560) to 77.8 g/100 g (for Z97/0474) in set 2. Peak viscosity values ranged between 295.6 RVU (rapid visco unit) (30572) and 467.0 RVU (01/1115) across clones in set 1 while for set 2, it ranged from 271.9 RVU (for 01/1404) to 471.3 RVU (for 01/1417). Significant differences (P < 0.05) existed in the proximate composition and pasting properties of the flour from different cassava genotypes investigated. The high peak viscosity exhibited by most genotypes is indicative that the flour may be suitable for products requiring high gel strength and elasticity. The proximate composition compares competitively with values obtainable from conventional clones.